2001
DOI: 10.1348/135910701169043
|View full text |Cite
|
Sign up to set email alerts
|

Psychological factors associated with short‐term recovery from total knee replacement

Abstract: As suggested by previous studies, coping style and locus of control appear to be important in the rehabilitation process. The current data suggest that psychological variables could be usefully included in a pre-operative assessment for total knee replacement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
1
7

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 23 publications
0
33
1
7
Order By: Relevance
“…Previous studies have shown that pain catastrophizing has a stronger correlation with mental components of health when compared to physical components (Severeijns, Vlaeyen, van den Hout, & Weber, 2001). Interestingly, however, we found no significant associations between our general measure of catastrophizing and physical aspects of health, a result that contrasts with other studies (AgarWilson & Jackson, 2012;de Boer, Struys, & Versteegen, 2012;Ferreira-Valente et al, 2011;Kendell, Saxby, To prevent inflation of alpha levels due to multiple testing, Bonferroni corrections were applied at each block; the *.05 and **.01 confidence levels were divided by the number of predictors in that block. Results show standardized betas Wong et al, 2011).…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies have shown that pain catastrophizing has a stronger correlation with mental components of health when compared to physical components (Severeijns, Vlaeyen, van den Hout, & Weber, 2001). Interestingly, however, we found no significant associations between our general measure of catastrophizing and physical aspects of health, a result that contrasts with other studies (AgarWilson & Jackson, 2012;de Boer, Struys, & Versteegen, 2012;Ferreira-Valente et al, 2011;Kendell, Saxby, To prevent inflation of alpha levels due to multiple testing, Bonferroni corrections were applied at each block; the *.05 and **.01 confidence levels were divided by the number of predictors in that block. Results show standardized betas Wong et al, 2011).…”
Section: Discussioncontrasting
confidence: 99%
“…While increasing age is commonly associated with greater functional disability (Hebert, Brayne, & Spiegelhalter, 1997;Rathouz, Kasper, & Zeger, 1998), our results indicated greater functional disability in the younger rehabilitation sample. This result is expected given that rehabilitation patients usually report pain following joint replacement surgery, particularly when undergoing daily physiotherapy exercise (Kendell et al, 2001) and joint pain would lead to greater perceived functional disability. Therefore, despite being older, the community-dwelling sample reported significantly lower levels of functional disability than the younger hospital sample.…”
Section: Discussionmentioning
confidence: 92%
“…For example, studies have shown that patients who catastrophize have higher levels of disability, 71 higher rates of health care usage, 28 longer hospitalizations, 29 increased pain medication usage, 38 and higher levels of motor pain behaviors, 48 and they take longer to reach rehabilitation milestones during surgical recovery. 53 Most of the findings regarding catastrophizing have been obtained in samples of patients with persistent pain drawn from pain clinics, specialized pain treatment programs, or medical/surgical clinics. Is pain catastrophizing a useful concept in understanding pain in individuals drawn from the general population?…”
Section: Pain Catastrophizingmentioning
confidence: 99%